2016
DOI: 10.1194/jlr.d065961
|View full text |Cite
|
Sign up to set email alerts
|

A continuous spectrophotometric assay that distinguishes between phospholipase A1 and A2 activities

Abstract: A new spectrophotometric assay was developed to measure, continuously and specifically, phospholipase A1 (PLA1) or phospholipase A2 (PLA2) activities using synthetic glycerophosphatidylcholines (PCs) containing α-eleostearic acid, either at the sn-1 position [1-α-eleostearoyl-2-octadecyl-rac-glycero-3-phosphocholine (EOPC)] or at the sn-2 position [1-octadecyl-2-α-eleostearoyl-rac-glycero-3-phosphocholine (OEPC)]. The substrates were coated onto the wells of microtiter plates. A nonhydrolyzable ether bond, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Thanks to the presence of β-cyclodextrin, the α-eleostearic acid released from EEPC is solubilized in the aqueous phase. This leads to an increase in the OD at 272 nm that is specific to α-eleostearic acid and allows estimating PLA activity ( El Alaoui et al, 2014 ; El Alaoui et al, 2016 ; Mendoza et al, 2012 ; Serveau-Avesque et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to the presence of β-cyclodextrin, the α-eleostearic acid released from EEPC is solubilized in the aqueous phase. This leads to an increase in the OD at 272 nm that is specific to α-eleostearic acid and allows estimating PLA activity ( El Alaoui et al, 2014 ; El Alaoui et al, 2016 ; Mendoza et al, 2012 ; Serveau-Avesque et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…These kinds of differences has been observed for example in the PLA activity determination of rGPLRP2 on C8-PC (1,2-dioctanoyl phosphatidylcholine) and egg PC with values of 551 ± 50 and 812 ± 100 U/mg, respectively, using the pH-stat technique in which the conditions assay consisted of a mechanically stirred emulsion of substrate previously emulsified by ultrasonic treatment ( Dridi et al, 2013 ). In other hand, the PLA activity of rGPLRP2 on coated EOPC (1-α-eleostearoyl-2-octadecyl- rac -glycero-3-phosphocholine) was reported with a value of 0.3 ± 0.02 U/mg ( El Alaoui et al, 2016 ), while the PLA activity of rGPLRP2 with the cHTS-PLA assay developed in this work was of 25.2 ± 0.9, about 84 times more compared with EOPC, and 32 times less compared to pH-stat technique using the same substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other phospholipase classes, the known PLA1 inhibitor is not commonly reported. The main strategy of PLA1 inhibition is to design a lipid mimetic compound or phospholipid bilayer derivatives [ 21 , 22 ] to compete with a substrate. The idea of the auxiliary site inhibition would be of interest because the site is a solvent-accessible surface.…”
Section: Discussionmentioning
confidence: 99%
“…Withers-Martinez et al have modelled a molecule of DGDG in the active site of the known 3D structure of a GPLRP2 chimera and the most favourable steric organization suggested that the ester bond at sn-2 position unlike the ester bond at sn-1 position could not be hydrolyzed by GPLRP2 [58]. More recent studies performed with synthetic acylglycerol substrates bearing non-hydrolysable bonds at sn-1 or sn-2 positions have however shown that rGPLRP2 can hydrolyze the ester bond at sn-2 position at a rate that is 10-fold lower compared to the hydrolysis of the ester bond at sn-1 position [59]. It is not known yet whether GPLRP2 displays a similar regioselective preference on galactolipids, but two hypotheses can be raised concerning the slow hydrolysis of C8-MGMG and the production of MGG observed during the enzymatic hydrolysis of C8-MGDG by rGPLRP2.…”
Section: Quantitative Analysis Of Mgdg Enzymatic Hydrolysismentioning
confidence: 99%